Exemple d'une recherche collaborative pour expérimenter l'usage du eportfolio - Nicole Monney; Nadia Cody
The support of a supervising teacher and university supervisors have a major role in the training of future teachers. In order to improve this support and professional development, the portfolio was introduced into a teacher education program. This paper presents the results of an empirical research carried out in collaboration with a team of multi-actors to structure an eportfolio and to test it. The first part defines the eportfolio and links it to the accompanying concept. Then, this paper describes the collaborative research design and the methods to collect data. The article ends with a reflection on structuring the eportfolio with practitioners and the need to ask existing activities before innovation.